The Association Between Recanalization, Collateral Flow, and Reperfusion in Acute Stroke Patients: A Dynamic Susceptibility Contrast MRI Study - Villringer, Kersten; Zimny, Sascha; Galinovic, Ivana; Nolte, Christian H.; Fiebach, Jochen B.; Khalil, Ahmed A. (Frontiers in Neurology, 2019)
Background: Collateral circulation in ischemic stroke patients plays an important role in infarct evolution und assessing patients’ eligibility for endovascular treatment. By means of dynamic susceptibility contrast MRI, we aimed to investigate the effects of reperfusion, recanalization, and collateral flow on clinical and imaging outcomes after stroke. Methods: Retrospective analysis of 184 patients enrolled into the prospective observational 1000Plus study (clinicaltrials.org NCT00715533). Inclusion criteria were vessel occlusion on baseline MR-angiography, imaging within 24 hours after stroke onset and follow-up perfusion imaging. Baseline Higashida score using subtracted dynamic MR perfusion source images was used to quantify collateral flow. The influence of these variables, and their interaction with vessel recanalization, on clinical and imaging outcomes was assessed using robust linear regression. Results: Ninety-eight patients (53.3%) showed vessel recanalization. Higashida score (p=0.002), and recanalization (p=0.0004) were independently associated with reperfusion. However, we found no evidence that the association between Higashida score and reperfusion relied on recanalization status (p=0.2). NIHSS on admission (p<0.0001) and recanalization (p=0.001) were independently associated with long-term outcome at 3 months, however, Higashida score (p=0.228) was not. Conclusion: Higashida score and recanalization were independently associated with reperfusion, but the association between recanalization and reperfusion was similar regardless of collateral flow quality. Recanalization was associated with long-term outcome. DSC-based measures of collateral flow were not associated with long-term outcome, possibly due to the complex dynamic nature of collateral recruitment, timing of imaging and the employed postprocessing.